The role of pharmaceutical industry in building resilient health system - Saxena, Kanika; Balani, Sunita; Srivastava, Pallavi (Frontiers in Public Health, 2022)
Objectives: This study explores the interrelationship among the current sustainability agenda of the pharmaceutical industry, based on United Nation Sustainable Development Goals (SDGs), the elements of the Joint External Evaluation Tool (JEE), and the triad components of One Health approach. Methods: A cross-walk exercise was conducted to identify commonalities among SDGs, JEE assessment tool and One Health approach. An in-depth study of 10 global pharmaceutical firms' corporate sustainability reports and COVID-19 response plan for 2019-20 was also conducted. Results: The result of the exercise showed the existence of a direct and indirect relationship among the SDGs, elements of JEE tool and One health approach. For example, both no poverty (SDG 1) and zero hunger (SDG 2) are linked with food safety targets under JEE and with human and animal health under One Health approach. Conclusion: This study adds a new dimension emphasizing on the possibility of tailoring the pharmaceutical industry’s activities under sustainability agenda to strengthen global health security while remaining consistent with the One Health approach.